Latent Syphilis Unresponsive to Doxycycline and Azithromycin - Cayadi Sidarta Antonius; Mutia Devi; M. Izazi Hari Purwoko; Suroso Adi Nugroho; Fitriani; Susanti Budiamal (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Syphilis management is based on the syphilis stage classification. The main treatment for syphilis is currently benzathine penicillin. However, patients allergic to penicillin antibiotics or who are not willing to be injected can be given doxycycline or erythromycin antibiotics. Case presentation. We present a case of a female with latent syphilis. Patient was previously treated with oral antibiotics, such as doxycycline for 30 days and followed by azithromycin for 30 consecutive days. Clinical laboratory examinations show increase of TPHA and VDRL, and the case was considered as unresponsive case. Later, the patients received benzathine penicillin G for three weeks and showed clinical improvement. Conclusion. For patient who refuse to be treated with penicillin injection, the alternative treatments are oral antibiotics. However, there is a reduced number of successful treatments for patients treated with oral antibiotics.